Pengaruh Mutasi Jabatan Terhadap Kepuasan Kerja Pegawai PT. PLN (Persero) Unit Induk Penyaluran dan Pusat Pengatur Beban (UIP3B) Sulawesi - Hapida, Nur; Hasbiah, Sitti; Dipoatmodjo, Tenri S.P (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the effect of job transfer on employee job satisfaction at PT. PLN (Persero) Sulawesi Main Distribution and Load Management Center Unit (UIP3B). The variables in this study consist of independent variables, namely job transfer and dependent variables, namely employee job satisfaction. The population in this study were all employees at PT. PLN (Persero) Sulawesi Main Distribution and Load Management Center Unit (UIP3B) totalling 135 people. The sampling technique used the Purpose sampling technique and used the Slovin formula in determining the number of samples. So the number of samples in this study was 70 people. The data collection techniques used were observation and questionnaires. The data analysis technique used was simple linear regression analysis with SPSS version 26 software to prove the hypothesis. The results of this study indicate that job transfer has a significant effect on employee job satisfaction at PT. PLN (Persero) Sulawesi Main Distribution and Load Management Center Unit (UIP3B).